ANALYSIS OF PERFORMANCE LOSSES CAUSED BY THE PLANE COLLISION WITH FOREIGN OBJECTS - Казак, В.; Бабенко, А. (Science-based technologies, 2010)
Analysis of performance losses caused by collision with any foreign objects provides an estimate direct and indirect economic losses and casualties caused by collision with any foreign objects, and continue to use the data to minimize economic losses, and prediction of dangerous situations and develop methods of preventing them.